STATUS, DISTRIBUTION AND RECENT CHANGES IN POPULATIONS OF CRITICALLY ENDANGERED GYPS INDICUS AND ENDANGERED NEOPHRON PERCNOPTERUS VULTURE SPECIES IN GWALIOR DISTRICT - Altaf Hussain Rather; Nasreena Shaban; Mohd Shafi Dar (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
Vultures, the most efficient carrion feeders play an important ecological role,but their number is declining at a very fast rate. The study on the status of vultures in Gwalior district was carried out in 2019 which revealed the presence of only two species of vultures, long billed vulture (Gyps indicus) and Egyptian vulture (Neophron percnopterus) in the study areas. A total of 29 individuals were recorded during the study period among which Gyps indicus was abundant in number. As per various study reports there has been a drastic decline in the population of vultures from the past 10-15 years due to many anthropogenic activities, veterinary use of diclofenac (DF), shortage of food and habitat loss. Therefore proper management and conservation measures should be taken to save these natural carrion consumers. This study is aimed at knowing the status and distribution of vulture population in Gwalior district which could enhance the contingent study, valuation will help in establishing the possible reasons for their decline and in turn will boost the steps for their conservation.